Risk of piperacillin‐induced hemolytic anemia in patients with cystic fibrosis and antipseudomonal treatment: a prospective observational study. Issue 12 (14th November 2019) - Roehmel, Jobst; Specht, Philip; Staab, Doris; Schwarz, Carsten; Salama, Abdulgabar; Mayer, Beate
Abstract : BACKGROUND: Drug‐induced immune hemolytic anemia (DIIHA) is a rare but severe side effect caused by numerous drugs. Case reports and case series suggest that piperacillin‐related DIIHA may be more common among patients with cystic fibrosis (CF). However, the prevalence is speculative. The aim of this prospective, observational study was determine the prevalence of DIIHA in such affected patients. METHODS AND MATERIALS: Patients with CF hospitalized for parenteral antibiotic therapy at Charité Universitätsmedizin Berlin, who had previously been exposed to IV antibiotics, were enrolled. Blood samples were collected on Days 3 and 12 of antibiotic treatment courses. Serological studies were performed using standard techniques with gel cards. Screening for drug‐dependent antibodies (ddab) was performed in the presence of the drugs and their urinary metabolites. RESULTS: A total of 52 parenteral antibiotic cycles in 43 patients were investigated. Ddab against piperacillin were detected in two patients (4.7%). The direct AHG was positive with anti‐IgG only in both patients. However only one of these patients developed mild immune hemolytic anemia. Both patients had been repeatedly treated with piperacillin without any evident hemolysis. There was no correlation between the exposure to piperacillin and the prevalence of ddab. CONCLUSION: Our prospective study indicates that piperacillin‐induced ddab occur more frequently in patients with CF than previously suggested. The question related to the significance of piperacillin‐dependent antibodies may reflect new aspects in this field.